Cost-effectiveness for KTE-X19 CAR T therapy for adult patients with relapsed/refractory mantle cell lymphoma in the United States. (1st January 2021) - Simons, Claire L.; Malone, Daniel; Wang, Michael; Maglinte, Gregory A.; Inocencio, Tim; Wade, Sally W.; Bennison, Craig; Shah, Bijal
Abstract: Aims: The objective of this study is to estimate the cost-effectiveness of KTE-X19 versus standard of care (SoC) in the treatment of relapsed/refractory (R/R) mantle cell lymphoma (MCL) patients from a US healthcare perspective. Materials and methods: A three-state partitioned-survival model (pre-progression, post-progression, and death) with a cycle length of 1 month was used to extrapolate progression-free and overall survival (OS) over a lifetime horizon. Due to the long tail of the OS curve, OS was modeled applying a mixture–cure methodology, using the assumption that patients whose disease had not progressed after 5 years experienced long-term remission. Population inputs were derived from the ZUMA-2 trial. This was also the source of KTE-X19 efficacy and safety data, while this data was obtained from the literature for SoC. Costs and resource use inputs were derived from the published literature and publicly available data sources. Health state utilities were derived from the ZUMA-2 trial (NCT02601313), applying the US tariff. Adverse event disutilities were derived from the published literature. Costs and health outcomes were discounted at 3% per year. The model estimated expected life years (LY), quality-adjusted life years (QALY), and total costs for KTE-X19 vs SoC. Deterministic and probabilistic sensitivity analyses were performed. Results: Median survival was 9.71 years for KTE-X19 and 2.13 for SoC. Discounted LYs, QALYs, and lifetime costs were 8.99, 7.39, and $693, 832 for KTE-X19 vs 4.47, 3.65, and $574, 263 for SoC, respectively. The KTE-X19 vs SoC cost per QALY was $31, 985. The most influential model parameter was the utility for patients with long-term remission. At a willingness-to-pay threshold of $150, 000 per QALY, the probability that KTE-X19 was cost-effective was 99%. Conclusion: The treatment of R/R MCL with KTE-X19 presents a potentially cost-effective alternative to the current SoC, deriving its value from incremental survival and health-related quality-of-life benefits.